Students’ Perceptions and Reflections on Project-Based Learning at SMP Negeri 31 Medan: A Qualitative Study of Engagement, Collaboration, and Learning Challenges - Fiber Yun Almanda Ginting (Jurnal Pendidikan: Media, Strategi, dan Metode, 2026)
Project-Based Learning (PjBL) has been increasingly promoted as a student-centered learning model that supports active participation, collaboration, creativity, communication, and problem-solving. However, the effectiveness of PjBL cannot be understood only from achievement scores because students’ perceptions and reflections provide important evidence about how the model is experienced in actual classroom learning. This study explores students’ perceptions and reflections on the implementation of PjBL at SMP Negeri 31 Medan, located at Jl. Jamin Ginting No. KM. 13, Lau Cih, Medan Tuntungan, Medan, North Sumatra. The study employed a qualitative descriptive design involving 25 students who responded to a 15-question interview instrument focusing on motivation, content understanding, teamwork, communication, problem-solving, creativity, confidence, teacher facilitation, project challenges, and future learning preferences. The data were analyzed using thematic analysis by identifying repeated patterns across student responses. The findings revealed ten major themes: increased motivation and engagement, better understanding of content, improved collaboration, enhanced communication skills, development of problem-solving skills, increased creativity, time management challenges, group coordination difficulties, positive perception of teacher facilitation, and strong support for future PjBL implementation. The most dominant theme was students’ support for future PjBL implementation, followed by collaboration skills and motivation. These findings indicate that students perceived PjBL as meaningful, practical, and engaging, although they also experienced challenges related to time, group coordination, unequal participation, and limited resources. The study concludes that PjBL can strengthen students’ learning engagement and 21st-century skills when supported by clear instructions, sufficient time, structured milestones, teacher facilitation, and fair group assessment.